Comparison of Round Window Anatomy between Pediatric and Adult Population: A Perspective from Cochlear Implantation Surgery - Pradhananga, Rabindra B; Gyawali, Bigyan R; Rayamajhi, Pabina (Journal of Institute of Medicine Nepal, 2020)
Introduction The round window is thought to be an ideal port for inserting electrodes during cochlear implantation. Considering its complex anatomy with an individual variation, this study aims to review the anatomy of round window based on the visibility of round window niche and round window membrane via posterior tympanotomy in pediatric and adult population who underwent cochlear implantation. Methods This was a retrospective observational study conducted at the Department of ENT-HNS, Institute of Medicine, Kathmandu, Nepal. Surgical notes of adult (>15 years) and pediatric cases (<15years) who underwent primary cochlear implantation from January 2015 to January 2018 were assessed for different grading of round window niche and round window membrane visibility via posterior tympanotomy. Cases with revision surgery and with incomplete documentation of intra-operative findings were excluded from the study. Statistical analysis was done using SPSS software version 25. We used Chi-square and Fisher’s exact tests to analyze the statistical association. Results Type B round window niche (partially visible) was the most common variant seen in the pediatric group while in adults, both Type B (partially visible) and Type C (fully visible) round window niche were common. Compared to the adults, the pediatric group had good visibility of RWM. However, there was no statistical association between these observations. Conclusion The round window has a wide range of anatomical variations with different levels of visibility of RWN and RWM in the different age groups. Although statistically insignificant, RWM visibility seemed to be better in pediatric cases compared to adults.